UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SOAL NON-RUTIN PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DENGAN PENERAPAN METODE PEER TUTORING [EFFORTS IN IMPROVING MATHEMATICAL PROBLEM-SOLVING SKILLS OF NON-ROUTINE PROBLEMS OF ONE-VARIABLE LINEAR EQUATIONS AND INEQUALITIES BY IMPLEMENTING THE PEER TUTORING METHOD] - Thamsir, Thalia; Silalahi, Destya Waty; Soesanto, Robert Harry (JOHME: Journal of Holistic Mathematics Education, 2019)
The purpose of learning mathematics is to obtain life skills through problem solving. Problem solving skills are one of mathematics skills that must be possessed by students. The result of the pre-cycle in this research showed that 83.33% of students had not achieved the minimum predicate “B-” in solving non-routine problems. It proved that students’ abilities in mathematics problem solving in non-routine problems were still low. During the pre-cycle, the researcher also observed some students who were not brave enough yet to ask questions of the teacher directly during the learning process. Besides that, almost all the students still had high individualistic and low awareness. Based on the problems that happened in the class, the researcher offered the peer tutoring method as a solution to improve students’ mathematical problem-solving skills in non-routine problems. The research method used in this research was Classroom Action Research using the Kemmis and McTaggart model. The instruments used in this research were tests, observation sheets, students’ questionnaires, and journal reflections. Based on the data analysis, students’ mathematical problem-solving skills in non-routine problems improved to 29.17% by implementing the peer tutoring method with the steps (1) choosing the tutors, (2) guiding the tutors, (3) students doing the tutoring activity, and (9) evaluating the learning processBAHASA INDONESIA ABSTRAK: Tujuan dari mempelajari matematika ialah untuk memperoleh kecakapan hidup salah satunya melalui pemecahan masalah. Kemampuan pemecahan masalah merupakan salah satu standar kemampuan matematika yang harus dimiliki oleh siswa. Hasil tes pra siklus pada penelitian ini menunjukkan sebanyak 83.33% siswa belum mampu mencapai predikat minimal ”˜B-’ dalam menyelesaikan soal non-rutin. Ini membuktikan bahwa kemampuan pemecahan masalah matematis siswa pada soal non-rutin masih kurang. Selama pra siklus berlangsung, peneliti juga mengamati beberapa siswa belum berani untuk bertanya langsung kepada guru selama proses pembelajaran berlangsung. Selain itu, sebagian besar siswa masih memiliki sikap individualis yang tinggi dan juga rasa kepedulian antar siswa masih rendah. Berdasarkan masalah yang terjadi di dalam kelas tersebut maka peneliti menawarkan metode peer tutoring sebagai solusi untuk meningkatkan kemampuan pemecahan masalah matematis siswa pada soal non-rutin. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas dengan model Kemmis dan Mc. Taggart. Instrumen yang digunakan pada penelitian ini adalah tes, lembar observasi, angket siswa dan jurnal refleksi. Berdasarkan analisis data, kemampuan pemecahan masalah matematis siswa pada soal non-rutin mengalami peningkatan hingga 29,17% menggunakan metode peer tutoring dengan langkah-langkah penerapan yaitu (1) memilih tutor, (2) membimbing tutor, (3) siswa melakukan kegiatan tutorial, dan (4) mengevaluasi pembelajaran